A prospective study of soluble receptor for advanced glycation end-products and colorectal cancer risk in postmenopausal women. (June 2016) - Chen, Liang; Duan, Zhigang; Tinker, Lesley; Sangi-Haghpeykar, Haleh; Strickler, Howard; Ho, Gloria Y.F.; Gunter, Marc J.; Rohan, Thomas; Logsdon, Craig; White, Donna L.; Royse, Kathryn; El-Serag, Hashem B.; et al.
Highlights: ⿢ The AGEs/RAGE axis is involved in obesity. ⿢ Soluble RAGE (sRAGE) can neutralize the detrimental effect mediated by AGEs/RAGE interaction. ⿢ sRAGE was inversely associated with risk of CRC among women with BMI ⿥ 25 kg/m 2 . ⿢ sRAGE may be a protective factor in obesity-related CRC in postmenopausal women. Abstract: Objectives: Receptor for advanced glycation end products (RAGE) expressed on adipocytes and immune cells can bind to ligand N ε -(carboxymethyl)-lysine (CML) and trigger dysregulation of adipokines and chronic inflammation. Soluble RAGE (sRAGE) mitigates the detrimental effect of RAGE. We examined the associations between circulating levels of CML-AGE and sRAGE and colorectal cancer (CRC). Methods: In a case-cohort study of the Women⿿s Health Initiative Study, blood levels of CML-AGE and sRAGE were measured using ELISA. We used multivariable Cox regression model to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) of incident CRC in relation to quartiles (Q) of biomarker levels. Results: Average follow-up was 7.8 years for 444 cases and 805 subcohort members. In the subcohort, CML-AGE and sRAGE were inversely correlated with BMI ( P values < 0.0001). Levels of CML-AGE and sRAGE were not associated with CRC. In BMI-specific analysis, the association between sRAGE and CRC was observed. Among women with BMI ⿥ 25 kg/m 2, those with highest levels of sRAGE had significantly lower risk for CRC as compared to women with lowest levels of sRAGE (HRQ4 versus Q1 : 0.39; 95% CI: 0.17⿿0.91). This inverse association was not observed among women with BMI <25 kg/m 2 ( P value for interaction = 0.01). Conclusions: Among postmenopausal women, the RAGE pathway may be involved in obesity-related CRC.